GE_GERICHTE C/10020/2010 vom 16. Oktober 2013 - GE Cour de justice (2013)
CONTRAT D'ENTREPRISE; PRIX DE L'OUVRAGE; RESPONSABILITÉ CONTRACTUELLE; ENTREPRENEUR; MANDATAIRE; HONORAIRES | CO.321a.1; CO.363; CO.364.1; CO.372.1; CO.373.1